Association of Metabolic Syndrome With Long-Term Cardiovascular Risks and All-Cause Mortality in Elderly Patients With Obstructive Sleep Apnea - Liu, Lin; Su, Xiaofeng; Zhao, Zhe; Han, Jiming; Li, Jianhua; Xu, Weihao; He, Zijun; Gao, Yinghui; Chen, Kaibing; Zhao, Libo; Gao, Yan; Wang, Huanhuan; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background Evidence suggests that an increased risk of major adverse cardiac events (MACE) and all-cause mortality is associated with obstructive sleep apnea (OSA), particularly in the elderly. Metabolic syndrome (MetS) increases cardiovascular risk in the general population; however, less is known about its influence in patients with OSA. We aimed to assess whether MetS affected the risk of MACE and all-cause mortality in elderly patients with OSA. Methods From January 2015 to October 2017, 1,157 patients with OSA, aged ≥60 years, no myocardial infarction (MI), and hospitalization for unstable angina or heart failure were enrolled at baseline and were followed up prospectively. OSA is defined as an apnea-hypopnea index of ≥5 events per hour, as recorded by polysomnography. Patients were classified on the basis of the presence of MetS, according to the definition of the National Cholesterol Education Program (NCEP). Incidence rates were expressed as cumulative incidence. Cox proportional hazards analysis was used to estimate the risk of all events. The primary outcomes were MACE, which included cardiovascular death, MI, and hospitalization for unstable angina or heart failure. Secondary outcomes were all-cause mortality, components of MACE, and a composite of all events. Results MetS was present in 703 out of 1,157 (60.8%) elderly patients with OSA. During the median follow-up of 42 months, 119 (10.3%) patients experienced MACE. MetS conferred a cumulative incidence of MACE in elderly patients with OSA (log-rank, P < 0.001). In addition, there was a trend for MACE incidence risk to gradually increase in individuals with ≥3 MetS components (P = 0.045). Multivariate analysis showed that MetS was associated with an incidence risk for MACE [adjusted hazard ratio (aHR), 1.86; 95% confidence interval (CI), 1.17–2.96; P = 0.009], a composite of all events (aHR, 1.54; 95% CI, 1.03–2.32; P = 0.036), and hospitalization for unstable angina (aHR, 2.01; 95% CI, 1.04–3.90; P = 0.039). No significant differences in the risk of all-cause mortality and other components of MACE between patients with and without MetS (P > 0.05). Subgroup analysis demonstrated that males (aHR, 2.23; 95% CI, 1.28–3.91, P = 0.05), individuals aged <70 years (aHR, 2.36; 95% CI, 1.27–4.39, P = 0.006), overweight and obese individuals (aHR, 2.32; 95% CI, 1.34–4.01, P = 0.003), and those with moderate-severe OSA (aHR, 1.81;95% CI: 1.05–3.12, P = 0.032) and concomitant MetS were at a higher risk for MACE. Conclusion MetS is common in elderly patients with OSA in the absence of MI, hospitalization for unstable angina or heart failure. Further, it confers an independent, increased risk of MACE, a composite of all events, and hospitalization for unstable angina. Overweight and obese males, aged <70 years with moderate-severe OSA combined with MetS presented a significantly higher MACE risk.